PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS MELALUI PEMBELAJARAN STRATEGI REACT PADA SISWA SMP - Syifa Syafira Al Ghifari; Eyus Sudihartinih (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2021)
This research aims to determine the improvement of mathematical critical thinking skills in junior high school students between students who get REACT (Relating, Experiencing, Applying Cooperating and Transferring) strategy learning with students who get direct instruction and find out student responses to learning with the REACT strategy. The research uses a quasi-experimental method with type of research was with Non-equivalent Pretest-Posttest Control Group Design. The population in this research were grade VIII students in even semester 2018/2019 in one of the state junior high school in the city of Bandung. The sampling technique was purposive sampling with a sample consisting of 2 classes, namely class VIII-A as a control class of 25 students and VIII-C as an experimental class as many as 26 students. Data collection obtained from the results of pretest and posttest. The results showed that the improvement of mathematical critical thinking skills through REACT strategy learning was significantly higher than direct learning. The increase in the learning outcomes of the experimental class students is in the medium category, while the increase in the control class students' learning outcomes is in the low category)